(untitled) (Asian Journal of Agriculture, 2020)
Abstract. Michael PS. 2020. Plants with modified anatomical structures capable of oxygenating the rhizosphere are threats to sulfidic soils under varying soil moisture regimes. Asian J Agric 4: 87-94. Acid sulfate soils (ASS) are naturally occurring soils, sediments or substrates formed under waterlogged, reducing conditions. These soils either contain sulfuric acid or have the potential to form it, in an amount that can have detrimental impacts on the environment. In general, ASS with sulfuric materials and that have acidified through oxidation of pyrite are referred to as sulfuric soils. ASS with sulfidic materials that contain pyrite and have the potential to acidify when exposed to air are referred to as sulfidic soils. In an undisturbed state below the water table, the sulfidic soils are benign, unless exposed due to various natural processes or anthropogenic activities. This study examined the importance of organic matter addition, plant macrophytes and turnover of organic matter from the plant macrophytes co-existing on pH, redox and sulfate content of sulfidic soil under flooded conditions. In almost all cases, organic matter without plants induced ameliorative effects. Presence of plants led to higher Eh values, low pH and higher sulfate contents, and acidified the sulfidic soil.